2023
DOI: 10.1021/acscentsci.3c01050
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemistry: A Hot Field with Opportunities for Cool Chemistry

Gregory D. Bowden,
Peter J. H. Scott,
Eszter Boros

Abstract: Recent Food and Drug Administration (FDA) approval of diagnostic and therapeutic radiopharmaceuticals and concurrent miniaturization of particle accelerators leading to improved access has fueled interest in the development of chemical transformations suitable for short-lived radioactive isotopes on the tracer scale. This recent renaissance of radiochemistry is paired with new opportunities to study fundamental chemical behavior and reactivity of elements to improve their production, separation, and incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 127 publications
0
2
0
Order By: Relevance
“…This treatment also induces several side effects such as gastrointestinal symptoms, hepatotoxicity, hematological anomalies (thrombocytopenia and leukopenia), or dermatological reactions (rash and pruritis). Radiopharmaceuticals based on metals have become essential tools in nuclear medicines: technetium-99m or gallium-68 are used on a daily basis worldwide for diagnostic imaging . Metalloantibiotics have also recently emerged as promising candidates in order to overcome antibiotic resistance …”
Section: Ru-based Therapeutic Agentsmentioning
confidence: 99%
“…This treatment also induces several side effects such as gastrointestinal symptoms, hepatotoxicity, hematological anomalies (thrombocytopenia and leukopenia), or dermatological reactions (rash and pruritis). Radiopharmaceuticals based on metals have become essential tools in nuclear medicines: technetium-99m or gallium-68 are used on a daily basis worldwide for diagnostic imaging . Metalloantibiotics have also recently emerged as promising candidates in order to overcome antibiotic resistance …”
Section: Ru-based Therapeutic Agentsmentioning
confidence: 99%
“…The ability of host molecules to encapsulate thallium cation could lead to new organic interesting chelators for delivering 201 Tl to specific tissues. [9] Our previous work revealed that the presence of hydroxyl functions was mandatory to sequester these two species, and that complexation efficiency increased with the number of hydroxyl functions. [6c-e] Moreover, increasing the size of the cavity decreased the complexation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting property of manganese complexes is the possibility of developing redox-responsive systems, taking advantage of the Mn­(II)/Mn­(III) pair . This strategy has been investigated for Mn-based MRI contrast agents, exploiting changes in 1 H relaxation enhancement effects upon varying the oxidation state of the metal ion. , Though application to radiochemistry could be more difficult, the development of the radiochemistry of redox-responsive Mn­(II)-based pharmaceuticals could pose an interesting challenge . Therefore, studying the electrochemistry of Mn­(II) complexes is an important assay to assess the properties of these systems.…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 Though application to radiochemistry could be more difficult, the development of the radiochemistry of redox-responsive Mn(II)-based pharmaceuticals could pose an interesting challenge. 21 Therefore, studying the electrochemistry of Mn(II) complexes is an important assay to assess the properties of these systems.…”
Section: Introductionmentioning
confidence: 99%